Subclinical finding in the perception of tactile sensation involvement after SARS-CoV2 infection: comparison with healthy controls using Semmes–Weinstein monofilament testing - Tereshko, Yan; Viotto, Chiara; Lettieri, Christian; Filon, Francesca Larese; Belgrado, Enrico; Merlino, Giovanni; Bovenzi, Massimo; Valente, Mariarosaria; Gigli, Gian Luigi; Dal Bello, Simone; Negro, Corrado; Ronchese, Federico (Frontiers in Neurology, 2023)
Background Post-acute COVID-19 syndrome patients complain of sensory alterations, mainly positive symptoms such as paresthesia or neuropathic pain but also decreased tactile sensation. Using the Semmes–Weinstein monofilament test (SWMT), our study aims to confront recently infected SARS-CoV2 subjects with a control group. Methods This is a cross-sectional, single-centric study. We performed the SWMT (North Coast Medical Inc.) on 30 patients with previous SARS-CoV2 infection (COVID group) and 46 controls (control group). These patients did not present comorbidities or sensory impairment and did not take any medications. The control group tested negative for SARS-CoV2 infection since the COVID-19 pandemic; the COVID group was examined for this study after the resolution of the infection. We tested the threshold of tactile sensation of the tips of the thumb, index, and little finger of each hand, one hand at a time; the dorsum and the hypothenar regions were also tested. Results Both groups presented the perception of tactile sensation within the reference value. Despite this result, subclinical changes suggestive of the involvement in peripheral sensory nerve function have been identified in the tested sites in the COVID group compared to the control group. The overall mean target force (grams) was higher in the COVID group than in the control group: 27 (7) vs. 19 (10) mg, p < 0.001. Conclusion Controls and the COVID group infection had normal tactile sensation thresholds. However, the COVID group presented a higher threshold than the control group, suggesting a possible subclinical perception of tactile sensation involvement of A-beta nerve fibers.